Optimized 4,5-diarylimidazoles as potent/selective inhibitors of protein kinase CK1δ and their structural relation to p38α MAPK - Halekotte, Jakob; Witt, Lydia; Ianes, Chiara; Krüger, Marc; Bührmann, Mike; Rauh, Daniel; Pichlo, Christian; Brunstein, Elena; Luxenburger, Andreas; Baumann, Ulrich; Knippschild, Uwe; Bischof, Joachim; et al. (Technische Universität Dortmund, 2017)
The involvement of protein kinase CK1δ in the pathogenesis of severe disorders such as Alzheimer’s disease, amyotrophic lateral sclerosis, familial advanced sleep phase syndrome, and cancer has dramatically increased interest in the development of effective small molecule inhibitors for both therapeutic application and basic research. Unfortunately, the design of CK1 isoform-specific compounds has proved to be highly complicated due to the existence of six evolutionarily conserved human CK1 members that possess similar, different, or even opposite physiological and pathophysiological implications. Consequently, only few potent and selective CK1δ inhibitors have been reported so far and structurally divergent approaches are urgently needed in order to establish SAR that might enable complete discrimination of CK1 isoforms and related p38α MAPK. In this study we report on design and characterization of optimized 4,5-diarylimidazoles as highly effective ATP-competitive inhibitors of CK1δ with compounds 11b (IC50 CK1δ = 4 nM, IC50 CK1ε = 25 nM), 12a (IC50 CK1δ = 19 nM, IC50 CK1ε = 227 nM), and 16b (IC50 CK1δ = 8 nM, IC50 CK1ε = 81 nM) being among the most potent CK1δ-targeting agents published to date. Inhibitor compound 11b, displaying potential as a pharmacological tool, has further been profiled over a panel of 321 protein kinases exhibiting high selectivity. Cellular efficacy has been evaluated in human pancreatic cancer cell lines Colo357 (EC50 = 3.5 µM) and Panc89 (EC50 = 1.5 µM). SAR is substantiated by X-ray crystallographic analysis of 16b in CK1δ and 11b in p38α.
Molecules;22(4)
Keywords: Protein kinase CK1; Formerly known as casein kinase 1; p38 MAPK; Kinase inhibitors; 4,5-diaryl-imidazoles; Alzheimer's disease; Amyotrophic lateral sclerosis; Familial advanced sleep phase syndrome; Cancer; 570; 540